Mutations Of Pro30Leu And Val281Leu Of The Cyp21 Gene In Patients Diagnosed With Ambiguous Genitalia. - Isa, M.N.; Muhamad, Y.K.; Fuziah, M.Z.; Rus Anida, A.; Sidek, M.Ros; Ramli, S.F. (2002)
Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders of adrenal steroidogenesis.